'It's Complicated': The Construction of Indian Middle-class Teens in Social Media. (July 2016) - Diwakar, Vaishali
After more than two decades as social media became regularized, domesticated and incorporated into our everyday life, we need to understand, both, how social media is shaped by and is shaping the practices humans use in interaction with, around and through it. With the advent of social media, everybody is affected, in one way or the other, by very ubiquity of new online expertise; children and young adults are usually among the first and keenest and passionate users of information and communication technologies. However, teens' voices are rarely acknowledged and considered effective in shaping the public discourse. This article claims that the new social media opens up the possibility for the young (13–17-year olds), of being part of the global world and at the same time being true to their roots and middle-class moralities. This article emphasizes that social networking sites act as a democratizing element which balances the power somewhat in favour of teens and helps them negotiate between being world class citizens and the torch bearers of Indian middle-class morality. This article explores their sense making of these often contradictory, yet connected, intersecting/overlapping, yet distinct, worlds.